Kayu Limbah Penebangan Intensitas Rendah di Izin Usaha Pemanfaatan Hasil Hutan Kayu-Hutan Alam - Ahmad Budiaman; Farikh Munir Mubarak; Winda Lismaya (Institut Pertanian Bogor, 2020)
Forest harvesting of natural-forest production in Indonesia is carried out with a high felling intensity, thus has changed the forest biomass. Several studies have shown a strong correlation between harvesting intensity and the reduction of wood volume in the forest. This condition may disrupt the stability of forest ecosystem. This study aimed to calculate and classificate logging residue of low-harvest intensity (one tree plots-1) in Indonesian Forest Concession. The study was conducted in private concessions in North Kalimantan and West Papua. Measurements were made in 30 dynamic circular sample plots with a radius of 2 times the height of the felled tree. The average size in North Kalimantan was 2.5 ha plot-1 and in West Papua was 1.5 ha plot-1. The sample plots were randomly placed in the cutting compartment. All logging residues with dbh ≥10 cm were measured after felling. The logging residue is classified into felled and unfelled trees and four types of logging residue (fallen tree, broken stem, stump, branches and twigs). The low felling intensity produced logging residue ranging from 4.98-5.55 m3 ha-1. The result indicated that logging residue came from felled trees (66%) was higher than those from unfelled trees (34%). The most common type of logging residue of felled tree was branches and twigs, broken stem and stump. The logging residue came from unfelled tree dominated by fallen tree followed by broken stem, branches, and twigs. Keywords: felling intensity, forest conservation, natural forest, selective cutting